Navigating The Metaverse: Exploring Its Pedagogical Affordances in Language Learning - Finita Dewi (Nusantara Science and Technology Proceedings, 2024)
In the digital transformation era with abundant technological advancement, the Metaverse emerged in education, providing opportunities for language learning like never before. This study aims to navigate the potential of the Metaverse by exploring its pedagogical affordances in facilitating language learners, looking into the educators’ strategies in designing lessons for immersive language learning experiences and describing the perceived benefits and challenges of learning language within the Metaverse space from the students’ perspectives. Using qualitative research design, this study dives into the pedagogical affordances of the Metaverse, examining the extent to which Metaverse engages and motivates learners, enhances language acquisition, fosters collaboration, and immerses students in a culturally relevant context. Furthermore, this study intends to illustrate the learning environment created by educators in facilitating language learning through Metaverse. Finally, students’ voices were generated to examine the practical implications of Metaverse-based language learning. This study contributes to the broader discourse on digital education by synthesizing the findings related to these research questions. It offers insights that can inform the future of language learning, aligning pedagogy with the possibilities of the Metaverse.